EFFECTS OF ROLE OVERLOAD, WORK ENGAGEMENT AND PERCEIVED ORGANISATIONAL SUPPORT ON NURSES’ JOB PERFORMANCE DURING THE COVID‐19 PANDEMIC - Bader Shahwan Alshammari , Thamer nawaf Alshammari , Ibrahim Yahya Ibrahim Tarshi, Mamdouh Saleem Alruwaili , Sultan Mardhi Alshammari (Chelonian Research Foundation, 2022)
The COVID-19 pandemic has placed extraordinary demands on nurses worldwide. This concurrent mixed methods study examined how role overload, work engagement, and perceived organizational support influenced nurse job performance across 170 bedside nurses at 5 hospitals in Saudi Arabia during the pandemic. Quantitative data revealed higher overload and lower engagement related to poorer performance. Qualitative interviews with 18 nurses emphasized how heavy workloads hindered effectiveness, while sufficient staffing, peer support, and management communication facilitated performance. Integrated results provide insights to guide nurse workforce strategies, well-being initiatives, and practice environment improvements through and beyond the pandemic. Findings underline the need to optimize engagement and control demands amidst crisis response to sustain provider performance essential for quality care delivery. Keywords: COVID-19; nurse job performance; work overload; employee engagement; mixed methods